Content Analysis of Comics on Line Webtoon - Nurohmah, Sintiya Putri; Putri, Ghina Fikriya; Imawan, Khaerudin; Lestari, Aghnia Dian (Rescollacom (Research Collaborations Community), 2024)
Technological advances produce a different culture of readers, there is a new culture of comic readers who change the way readers read comics, as a result of technological advances it created a digital platform published online called LINE Webtoon, so that it can be identified the purpose in this article to know the presentation of comic content on LINE webtoon or website and cartoon by facilitating readers who no longer read without having to buy comics in physical form but already using the application. This research uses a descriptive qualitative method by looking at LINE webtoon to find out the presentation of comic content on LINE webtoon, which is supported using McCloud's Making Comic theory. The results of this study suggest that the experience of reading comics on LINE Webtoon has a variety of attractions, readers' factors in reading comics can also be influenced by social and cultural interactions around them, for example if a comic is trending or widely discussed on social media, readers tend to be interested in trying to read it as well as being influenced by comic content and comic authors themselves such as with emotionally evocative storylines and strong characters, tend to be more captivating and make readers come back to read the next episode, by paying attention to these aspects, it can be seen how works of fine art in the form of comics can create interesting comic content.